Efficacy of Acceptance and Commitment Therapy on Psychological Health and Inflexibility among Mothers of Children with Cerebral Palsy - Damilola Adepeju Olayinka-Aliu (‎‎‎TAZKIYA Journal of Psychology, 2022)
Caregiving may be a burden to the Psychological Health (PH) of mothers of children with Cerebral Palsy (CP). However, little attention is given to psychotherapeutic intervention in managing mothers caring for such children in Nigeria. This study, therefore, investigated the efficacy of Acceptance and Commitment Therapy (ACT) among mothers of children with CP accessing therapeutic outpatient services at Federal Psychiatric Hospital (FPH) Lagos, Nigeria. This research follows a quasi-experimental type with pre-test, post-test plans, and control group. Accordingly, 30 people were selected through volunteered sampling among mothers of children with CP accessing therapeutic outpatient services at child/adolescent unit of Federal Psychiatric Hospital. Then, they were randomly placed into two groups of 20 (experimental and control) each and evaluated using research tools. Research tools consisted of Acceptance and Action Questionnaire (AAQ-II) and Cerebral Palsy Psychological Health Scale (CPPHS) whose reliability and validity have been confirmed in previous studies. Research data were analysed using the analysis of covariance (ANCOVA). The statistical analysis confirmed the difference in the components of psychological health and acceptance level/psychological flexibility in the experimental group, which had received acceptance and commitment therapy compared to the group that had not received any therapy in this regard (control group) (p<.05). The ACT had significant effect on Psychological Health {F (1.36) =7.94} after controlling for severity of illness and parental knowledge. Participants in experimental group improved in their Psychological Health when compared with those in control group {t(38) = 3.20}. Acceptance level/ psychological flexibility of the mothers improved after intervention with a decrease in pretest mean score (= 31.60) to posttest mean score (= 24.10). Acceptance and commitment therapy improves psychological health